2001
DOI: 10.1211/0022357011775596
|View full text |Cite
|
Sign up to set email alerts
|

The development and in-vitro evaluation of novel mixed metal hydroxy-carbonate compounds as phosphate binders

Abstract: The currently available phosphate binders are relatively inefficient and suffer from clinical side-effects of increased absorption of calcium and aluminium and the diarrhoea-inducing effects of magnesium. A new class of compounds based on mixed metal hydroxides has been developed and evaluated for their potential as phosphate binders. The mixed metal hydroxides were prepared using a standard procedure for hydrotalcite (Al2Mg6(OH)16.CO3.4H2O) by substituting Fe3+ for Al3+, with Mg2+ or Ca2+ as the divalent meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…CC bound more phosphate in acidic conditions, which is in concurrence with the previous literature, probably because of its optimum solubility in an acidic milieu . Similar effects were demonstrated with concomitant use of pantoprazole and CC in vivo where serum phosphate was higher in the group using both CC and pantoprazole …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…CC bound more phosphate in acidic conditions, which is in concurrence with the previous literature, probably because of its optimum solubility in an acidic milieu . Similar effects were demonstrated with concomitant use of pantoprazole and CC in vivo where serum phosphate was higher in the group using both CC and pantoprazole …”
Section: Discussionsupporting
confidence: 90%
“…Although, in a randomized clinical trial in haemodialysis patients using SH only or SH and pantoprazole, no significant difference between phosphate levels was observed. 13 CC bound more phosphate in acidic conditions, which is in concurrence with the previous literature, 17,23 probably because of its optimum solubility in an acidic milieu. 7 Similar effects were demonstrated with concomitant use of pantoprazole and CC in vivo where serum phosphate was higher in the group using both CC and pantoprazole.…”
Section: Influence Of Phsupporting
confidence: 91%
“…Their use as phosphate binders was first reported in this laboratory. We have previously shown that MMHs based on CaFe and MgFe can bind phosphate in solution 40,41. In the present study, we have investigated further the effect of different Mg 2+ :Fe 3+ ratios and preparations, such as aging and drying, on their phosphate binding performances in order to optimize the product.…”
Section: Discussionmentioning
confidence: 93%
“…The phosphate-binding capacity of iron was first recognized in experimental and animal studies (21)(22)(23). Iron is a cation that binds phosphate in the NOVEL THERAPEUTIC OPTIONS FOR THE TREATMENT OF MINERAL METABOLISM ABNORMALITIES GI tract and results in increased phosphate excretion in feces.…”
Section: Iron-based Phosphate Bindersmentioning
confidence: 99%